Bioelectrocatalytic carbon dioxide reduction by an engineered formate dehydrogenase from Thermoanaerobacter kivui - Weisong Liu; Kuncheng Zhang; Jiang Liu; Yuanming Wang; Meng Zhang; Huijuan Cui; Junsong Sun; Lingling Zhang (Nature Communications)
Abstract Electrocatalytic carbon dioxide (CO2) reduction by CO2 reductases is a promising approach for biomanufacturing. Among all known biological or chemical catalysts, hydrogen-dependent carbon dioxide reductase from Thermoanaerobacter kivui (TkHDCR) possesses the highest activity toward CO2 reduction. Herein, we engineer TkHDCR to generate an electro-responsive carbon dioxide reductase considering the safety and convenience. To achieve this purpose, a recombinant Escherichia coli TkHDCR overexpression system is established. The formate dehydrogenase is obtained via subunit truncation and rational design, which enables direct electron transfer (DET)-type bioelectrocatalysis with a near-zero overpotential. By applying a constant voltage of −500 mV (vs. SHE) to a mediated electrolytic cell, 22.8 ± 1.6 mM formate is synthesized in 16 h with an average production rate of 7.1 ± 0.5 μmol h−1cm−2, a Faradaic efficiency of 98.9% and a half-cell energy efficiency of 94.4%. This study provides an enzyme candidate for high efficient CO2 reduction and opens up a way to develop paradigm for CO2-based bio-manufacturing.